PENINGKATAN POTENSI BATU PADAS LADGESTONE SEBAGAI ADSORBEN ION LOGAM BERAT Cr(III) DALAM AIR MELALUI AKTIVASI ASAM DAN BASA - N. P. Diantariani (Jurnal Kimia (Journal of Chemistry), 2010)
The research with aim to increase potency of natural batu padas of Ladgestone type through activation usedby acid (H2SO4) and basa (NaOH) various concentrations (2.0; 4.0; and 6.0N) to adsorption ability of heavy metalion of Cr(III) in water have been done. Acid and base activated batu padas was characterizated of specific surfacearea with blue methylen method, whereas surface acidity determined by acid-base titration. Whereas, amount ofCr(III) which can of maximum adsorpted every weight of adsorben or adsorption capacity determined by atomicabsorption spectrophotometer (AAS). The result measurement of activated batu padas compared by batu padaswithout activation (control).Result of research indicate that batu padas after activated by NaOH and of H2SO4 yield surface acidity(active sites) and realtive higher specific surface area compared with without activation (control). Maximumability(capacity) adsorption to Cr(III) was just increasing for NaOH activated batu padas. Highest Capacitiesobtained by NaOH activated batu padas at concentration 4.0N was 2.0265 mg/g.